EXECUTIVE SMOKING BAN EQUALS BAD POLITICS (Tufts Archival Research Center, 2007)
Copy; Release detailing proposed executive order on banning smoking in federal buildings. Attributes idea to HHS Secretary Sullivan and Office of Management and Budget (OMB). Enumerates reasons why order would be politically disastrous, including failure to recognize the rights of a minority, ignorance of collective bargaining and labor rights, and the relative haste at which the order is being crafted. Claims that Administration needs votes of "Tobaccoland" states in Congress.